Experimental and numerical study on bending properties of heterogeneous lamella layups in cross laminated timber using Australian Radiata Pine. (30th June 2020) - Li, Xin; Ashraf, Mahmud; Subhani, Mahbube; Kremer, Paul; Kafle, Bidur; Ghabraie, Kazem
Highlights: Radiata Pine manufactured cross laminated timber (CLT) using heterogeneous lamella were investigated. There was a good agreement in bending results of CLT between the theoretical methods and experimental tests. Developed FE modelling technique could capture the structural performance of CLT. Improved bending performance was observed for panels with thinner thickness. Abstract: Cross laminated timber (CLT) is a sustainable and innovative engineered timber product validated as a viable alternative to more traditional construction materials like reinforced concrete and steel for use in mid-rise prefabricated construction. The structural response of CLT heavily relies on the species of timber used in manufacturing with feedstock varying significantly due to the original source and plantation stand. In Australia, Radiata Pine commonly used for general purpose structural timber mainly in residential house framing. Australia's largest CLT manufacturer, XLam, use Radiata Pine to produce panels for prefabricated construction. The present paper investigates the out-of-plane bending behaviour of 24 XLam CLT panels utilising four-point loading configurations. Experimental results indicated brittle failure modes when the samples were loaded along both the major and minor axes. In addition, plane cross-sections remain plane assumption were confirmed from the strain data obtained from the experimental tests. Various analytical methods (Timoshenko, Gamma ( γ ), K, and Shear Analogy methods) assessed the bending properties of the test samples, with the shear analogy method yielding the most accurate prediction. Other theoretical methods produced reasonable outcomes in accessing the effective bending stiffness together with bending and shear strengths. Finally, the bending properties of CLT were investigated using finite element analysis, which capture the overall behaviour of Radiata Pine CLT panels adequately. The effect of panel thickness was then examined numerically to observe its effect on bending.